Access to transplantation for persons with intellectual disability: Strategies for nondiscrimination. Issue 8 (18th January 2020) - Chen, Ashton; Ahmad, Mahwish; Flescher, Andrew; Freeman, William L.; Little, Stephanie; Martins, Paulo N.; Veatch, Robert M.; Wightman, Aaron; Ladin, Keren
Abstract : Disqualifying patients with intellectual disabilities (ID) from transplantation has received growing attention from the media, state legislatures, the Office of Civil Rights, and recently the National Council on Disability, as well as internationally. Compared with evidence‐based criteria used to determine transplant eligibility, the ID criterion remains controversial because of its potential to be discriminatory, subjective, and because its relationship to outcomes is uncertain. Use of ID in determining transplant candidacy may stem partly from perceived worse adherence and outcomes for patients with ID, fear of penalties to transplant centers for poor outcomes, and stigma surrounding the quality of life for people with ID. However, using ID as a contraindication to solid organ transplantation is not evidence‐based and reduces equitable access to transplantation, disadvantaging an already vulnerable population. Variability and lack of transparency in referral and evaluation allows for gatekeeping, threatens patient autonomy, limits access to lifesaving treatment, and may be seen as unfair. We examine the benefits and harms of using ID as a transplant eligibility criterion, review current clinical evidence and ethical considerations, and make recommendations for transplant teams and regulatory agencies to ensure fair access to transplant for individuals with ID. Abstract : This article examines the controversy surrounding use of intellectual disability as a criterion for transplant eligibility, weighing the benefits and harms, reviewing current clinical evidence and ethical considerations, and offering recommendations for transplant teams and regulatory agencies to ensure fair access to transplant for individuals with intellectual disabilities.